1989
DOI: 10.1007/bf02365551
|View full text |Cite
|
Sign up to set email alerts
|

Zur chemischen Zusammensetzung der CtenophorePleurobrachia pileus in der Kieler Bucht

Abstract: On the chemical composition of the ctenophore Pleurobrachia pileus in Klel Bight.The chemical composition of the ctenophore Pleurobrachia pfleus was investigated in March, May and July 1981 in Kiel Bight, western Baltic. The results of all determinations yielded low values compared with other zooplankton groups. Dry weight made up 1.95 to 2.28 % wet weight with a minimum occurring in May. Ash-free dry weight amounted to 28-37 % of the dry weight but exhibited a maximum in May. Carbon and nitrogen analyses yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…According to Dudkin et al (2002), Beroe in the course of the starvation has utilized glucose and metabolic carbohydrates most intensively especially in comparing with the utilization of protein and of structural carbohydrates. These changes in the biochemical composition of starved specimens of both B. ovata and M. leidyi in general did not differ from those that were observed in the ctenophore Pleurobrachia pileus from the North Sea (Hoeger, 1983;Schneider, 1989).…”
Section: Discussionmentioning
confidence: 39%
See 3 more Smart Citations
“…According to Dudkin et al (2002), Beroe in the course of the starvation has utilized glucose and metabolic carbohydrates most intensively especially in comparing with the utilization of protein and of structural carbohydrates. These changes in the biochemical composition of starved specimens of both B. ovata and M. leidyi in general did not differ from those that were observed in the ctenophore Pleurobrachia pileus from the North Sea (Hoeger, 1983;Schneider, 1989).…”
Section: Discussionmentioning
confidence: 39%
“…Although, there is supposition, that for some species the total lipid could be an exception in this respect (Schneider, 1989): sometimes their large amounts testified rather to starvation than provision of feeding for ctenophores (Figures 4-6).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…So, the hypothesis based on the study of Borodkin and Korzhikova (1991), that due to their relatively high phosphorus content Pleurobrachia, or perhaps even all ctenophores, is expected to show phosphorus limitation quickly, clearly needs to be rejected. In fact, several studies (Schneider 1989;Anninsky et al 2005) have indicated a very high content of proteins in ctenophores, which is corroborated by the low C:N values found by Kremer and coworkers (Kremer 1977(Kremer , 1982Kremer et al 1986;Youngbluth et al 1988), so the measurements of Borodkin and Korzhikova (1991) for Mnemiopsis leidyi might be considered unusual and not reflect a general pattern in ctenophores. Virtually no information exists on the nutrient stoichiometry and physiology of ctenophores, and of P. pileus in particular.…”
Section: Discussionmentioning
confidence: 84%